Objetivo da firma e crescimento : um estudo em empresas de base tecnológica - Santos, Daniela Tatiane dos (2007)
This dissertation intends to analyze the growth of Technology Based Firms (TBFs) in Brazil linking it with the objectives pursued for them. The TBFs are technologically dynamic companies, with a dense knowledge base that carry throughout radical or incremental technological innovations. Considering the intensity of their technological effort, high growth is expected. However, empirical studies evidence growth records are usually rather moderate. The explanations for this paradox use to emphasize some factors characterized as barriers to growth. Recently, another explicative hypothesis was postulated, concerning to complex configuration of firms objectives and its impact on TBFs growth trends. Thus, this research aims to analyze the objectives of TBFs in Brazil, stressing the importance of growth among them. The empirical research has benefited from available information on the Technology Management Group database (GeTec/UFSCar) on TBFs and in a questionnaire that was sent to a sample of EBTs.